Designing a packed column for ammonia recovery : evaluating two packing types - Pérez Sánchez, Amaury (2025)
Fil: Pérez Sánchez, Amaury. Universidad de Camagüey “Ignacio Agramonte Loynaz”. Facultad de Ciencias Aplicadas; Cuba.